2010
DOI: 10.1007/s11104-010-0445-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrate—ammonium ratio on growth and nutrition of Arabidopsis thaliana

Abstract: Arabidopsis thaliana seedlings were grown in hydroponic culture under controlled conditions in mediums with different NO 3 − /NH 4 + ratios. The mediums were not buffered, against pH change, but their pH was reset at pH 5.5 each 2 days. When ammoniacal N source was predominant, the whole plant biomass deposition was diminished, parallely to several parameters which revealed degraded leaf physiological status, such as leaf chlorosis associated with diminished chlorophyll content, lowered K + , Ca 2+ , and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 48 publications
1
26
0
3
Order By: Relevance
“…This resulted from the membrane damage and cell wall breakage, which increase cell electrolyte leakage (Kochanová et al, 2014). Similar effect was observed in plants of Arabidopsis thaliana (Helali et al, 2010), Brassica oleracea (Barreto et al, 2017), and S. lycopersicum (Barreto et al, 2018) cultivated under high NH4 + concentrations. In contrast, plants under high NH4 + concentration that received Si fertilization had lower electrolyte leakage index than plants without Si (Figure 2b).…”
Section: Plant Physiological Parametersmentioning
confidence: 58%
“…This resulted from the membrane damage and cell wall breakage, which increase cell electrolyte leakage (Kochanová et al, 2014). Similar effect was observed in plants of Arabidopsis thaliana (Helali et al, 2010), Brassica oleracea (Barreto et al, 2017), and S. lycopersicum (Barreto et al, 2018) cultivated under high NH4 + concentrations. In contrast, plants under high NH4 + concentration that received Si fertilization had lower electrolyte leakage index than plants without Si (Figure 2b).…”
Section: Plant Physiological Parametersmentioning
confidence: 58%
“…Supplying the two forms of nitrogen in a specific ratio will lead to the optimum growth; this finding has been reported in species such as apple (Malus domestica Borkh) [18,19], tomato (Solanum lycopersicum L.) [20,21], and rice (Oryza sativa L.) [22][23][24]. Predominant sources of ammonia N may also negatively affect the whole plant biomass deposition in some species, such as Arabidopsis thaliana [25,26]; while in another study, Arabidopsis plants displayed the potential of stimulating glucosinolate metabolism with ammonium nutrition [27]. An appropriate ammonium-nitrate ratio can enhance plant tolerance to abiotic stresses.…”
Section: Introductionmentioning
confidence: 83%
“…Studies based in ammonium stress in Arabidopsis have generally described Chl content reduction as a toxicity symptom. 17,18 However, Chl content increase has been also reported. 19 Interestingly, Li et al 20 showed that under mixed nutrition (5 mM NO 3 ¡ supplemented with increasing concentrations of NH 4 C ) Arabidopsis cv.…”
Section: Mild Ammonium Stress Increases Chlorophyll Content In Arabidmentioning
confidence: 99%